2019
DOI: 10.1299/mej.19-00297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron addition on mechanical properties of Fe-Ni-Mo-B-C sintered alloys

Abstract: Sintered materials are superior in productivity because of their simple process, but their mechanical properties are low. To improve the mechanical properties of sintered materials, we focus on liquid-phase sintering. In this study, we selected boron as sintering aids and evaluated on the effect of the addition quantity of boron (0-0.6 mass%) to the mechanical properties of liquid-phase sintered and heat-treated materials. In the test range of this study, the tensile strength of material with an additional qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…There have been some reports regarding to the effect of Cu, Ni or Mn on the microstructure and properties of the Fe-B-C alloys [16][17][18][19]. However, their examined compositions have been limited up to 3 wt.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some reports regarding to the effect of Cu, Ni or Mn on the microstructure and properties of the Fe-B-C alloys [16][17][18][19]. However, their examined compositions have been limited up to 3 wt.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have developed a liquid phase sintering method achieving high density without secondary processing, for the purpose of achieving both high strength and low cost (Egashira et al, 2019;Egashira et al, 2020). In our previous study, the effect of the addition of boron on the rolling contact fatigue strength of the Fe-Ni-Mo-B-C sintered and carburized materials has been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…[31,32] Likewise, the addition of the appropriate alloying elements was beneficial to the densification of boron-containing alloys; however, the improvement of elongation property was very limited because a large amount of liquid phase produced the continuous network of eutectic hard phases [M 23 B 6 , M 3 (C, B), and M 2 B] at the grain boundaries. [33,34] Recently, the mechanical properties of liquid phase sintered alloys have been studied based on the microstructural modification, which prevented the continuous network of eutectic phases and increased the grain continuity. [35][36][37] Several studies suggested that the microstructure of boron-containing alloys can be modified by composition [9,12] and heat treatment.…”
Section: Introductionmentioning
confidence: 99%